Creativity caged in translation: a neo-institutional perspective on crisis communication - Fredriksson, Magnus; Olsson, Eva Karin; Pallas, Josef (Instituto de Investigación en Relaciones Públicas, 2014)
Crisis communication research has primarily focused on universal models guiding managers of various organisations in times of crisis. Even though this is about to change, a tendency remains for research in the field to overlook the impact of structural conditions on organisation’s crisis communication. In order to add to the emergent discussion on new theoretical and empirical venues within the field of crisis communication, this paper proposes a framework based on new institutional theory for analysing crisis communication practices as a societal phenomenon. New institutionalism is advocated due to its ability to shift the focus from agency to structure and in doing so emphasise the social preconditions for organisational activities. In line with this, this conceptual paper discusses crisis communication as an institution, i.e., as a set of more or less conscious ideas about formats (the organisational structures developed for crisis communication work), contents (the content of organisations’ communication in times of crisis) and contexts (the situations during which organisations are expected to perform crisis communication). Moreover, we discuss how these ideas become translated (i.e., modified) as they travel (i.e., become legitimate, popular and get widely spread) across organisational and institutional contexts. In order to illustrate the framework described above, the Swedish authorities’ communication in connection to the A/H1N1 outbreak is used as a case study.
La creatividad enjaulada en la traducción: una perspectiva neoinstitucional sobre la comunicación de crisis
Keywords: Relaciones públicas; Comunicación en la empresa; Public Relations; Crisis communication; Neo-institutional theory